Warfare and welfare military conflict and welfare state development in Western countries - Obinger, Herbert 1970-; Petersen, Klaus 1965-; Starke, Peter 1977- (Oxford University Press, 2018)
While the first half of the 20th century was characterized by total war, the second half witnessed, at least in the Western world, a massive expansion of the modern welfare state. A growing share of the population was covered by ever more generous systems of social protection that dramatically reduced poverty and economic inequality in the post-war decades. With it also came a growth in social spending, taxation and regulation that changed the nature of the modern state and the functioning of market economies. Whether and in which ways warfare and the rise of the welfare state are related, is subject of this volume. Distinguishing between three different phases (war preparation, wartime mobilization, and the post-war period), the volume provides the first systematic comparative analysis of the impact of war on welfare state development in the western world
Keywords: Geschichte 1860-1960; War and society; Welfare state / History / 20th century; Bewaffneter Konflikt; Kriegführung; Wohlfahrtsstaat; Aufsatzsammlung